Insulin receptor substrate in brain-enriched exosomes in subjects with major depression: on the path of creation of biosignatures of central insulin resistance - Nasca, Carla; Dobbin, Josh; Bigio, Benedetta; Watson, Kathleen; de Angelis, Paolo; Kautz, Marin; Cochran, Ashly; Mathé, Aleksander A.; Kocsis, James H.; Lee, Francis S.; Murrough, James W.; McEwen, Bruce S.; et al. (Molecular psychiatry, 2021)
Insulin signaling is critical for neuroplasticity, cerebral metabolism as well as for systemic energy metabolism. In rodent studies, impaired brain insulin signaling with resultant insulin resistance (IR) modulates synaptic plasticity and the corresponding behavioral functions. Despite discoveries of central actions of insulin, in vivo molecular mechanisms of brain IR until recently have proven difficult to study in the human brain. In the current study, we leveraged recent technological advances in molecular biology and herein report an increased number of exosomes enriched for L1CAM, a marker predominantly expressed in the brain, in subjects with major depressive disorder (MDD) as compared with age- and sex-matched healthy controls (HC). We also report increased concentration of the insulin receptor substrate-1 (IRS-1) in L1CAM + exosomes in subjects with MDD as compared with age- and sex-matched HC. We found a relationship between expression of IRS-1 in L1CAM + exosomes and systemic IR as assessed by homeostatic model assessment of IR in HC, but not in subjects with MDD. The increased IRS-1 levels in L1CAM + exosomes were greater in subjects with MDD and were associated with suicidality and anhedonia. Finally, our data suggested sex differences in serine-312 phosphorylation of IRS-1 in L1CAM + exosomes in subjects with MDD. These findings provide a starting point for creating mechanistic framework of brain IR in further development of personalized medicine strategies to effectively treat MDD.